Development of a biomorphic and hyper-redundant caecilian based robots - Fabico, Karl (Animo Repository, 2017)
This paper presents the development and design of a mobile multilink robot. Because of its multilink property, snake robots are appropriate in tight and hard to reach places. This is robot is intended to be deployed in such areas specifically in disaster rubbles. The robot is composed of 10 segments each of which has one degree of freedom. The robot is equipped with proximity sensors for obstacle detection and IMU for orientation sensing. In front of the robot, a wireless camera is attached so that the environment where the robot operates is viewed by the base controller. Experiments showed that the movement algorithm which follows the snake's biological motion is successfully implemented with a maximum movement velocity of 70cm/s. The maximum climb height is 22cm. This study demonstrates the effectiveness of the snake robot in different terrain with obstacles and small obstacle gaps. © 2017 IEEE.